Primordial Dark Energy from a Condensate of Spinors in a 5D Vacuum - Pablo Alejandro Sánchez; Mauricio Bellini (Advances in High Energy Physics)
We explore the possibility that the expansion of the universe can be driven by a condensate of spinors which are free of interactions in a 5D relativistic vacuum defined in an extended de Sitter spacetime which is Riemann flat. The extra coordinate is considered as noncompact. After making a static foliation on the extra coordinate, we obtain an effective 4D (inflationary) de Sitter expansion which describes an inflationary universe. We found that the condensate of spinors studied here could be an interesting candidate to explain the presence of dark energy in the early universe. The dark energy density which we are talking about is poured into smaller subhorizon scales with the evolution of the inflationary expansion.